Operation risk assessment of Flexible Manufacturing Networks subject to quality-reliability coupling - Wang, Xin; Ke, Yongwei; Cai, Zhiqiang; Ye, Zhenggeng (Reliability engineering & system safety, 2024)
In flexible manufacturing network (FMN), the growth of product types increases the diversity of interacting behaviors between machine reliability and product quality, and the product diversity and machine flexibility promote the explosion of processing routes and processing sequences, increasing the gap between current risk evaluation of manufacturing systems and engineering practice. To fill this gap, a novel operation risk assessment framework is constructed for the complex FMN. In detail, to model the reliability-quality interactions, a mathematical framework describing a complete manufacturing process involving "feedstock quality (Q1) - machine degradation (R) - product processing quality (Q2) - quality inspection status (I)" is proposed for complex FMN, solving the measurement of interacting behaviors between machine reliability and product quality in an FMN that suffers from both multiple process routes and multi-type products. Then, an effective evaluation framework is proposed to evaluate the connectivity risk of multiple process routes and the quality risk of multiple product types in a complex FMN, providing a concurrent solution for risk evaluation under both complex system structures and complex quality-reliability interrelationships. At last, a simulation experiment verifies the effectiveness of our proposed methods and reveals differences in the operation risk of different product types in an FMN.